Spillovers to and from the Nordic Economies : A Macroeconometric Model Based Analysis - Vitek, Francis (IMF Working Papers; Working Paper ;, 2013)
This paper analyzes the transmission of shocks and policies among and across the Nordic economies and the rest of the world. This spillover analysis is based on a pair of estimated structural macroeconometric models of the world economy, disaggregated into thirty five national economies. We find that the Nordic economies are heavily exposed to external macroeconomic and financial shocks, but have significant scope to mitigate their domestic macroeconomic impacts through coordinated policy responses, given their high degree of regional integration.